Application of nano aluminum in modified EDM: pmedm - Abdul-Rani, A.M. (Asian Research Publishing Network, 2016)
This research was conducted to investigate the effect of nano aluminum mixed with electrical discharge machining dielectric on surface roughness (Ra), corrosion rate and material removal rate (MRR) of titanium alloy. Conventional machining of titanium alloy is a challenge even when using non-conventional machining processes such as electrical discharge machining (EDM). Among the limitations of EDM are machined surface alteration, induced corrosion, low material removal rate and residual stress during the EDM process. A newly developed and improved EDM process known as powder mixed electrical discharge machining (PMEDM) is envisaged able to address some of the above mentioned problems. In this study, PMEDM machining performance on titanium alloy workpiece using nano aluminum powder is assessed to investigate its improvement for biomedical application. Machining process parameters such as peak-current, ON-time, gap voltage and nano aluminum concentration are varied when machining biomedical grade titanium alloy. PMEDM although still is its infancy has shown slight improvement in Ra, corrosion rate and material removal rate. MRR is improved about more than 33.33 due to effect of nano aluminum concentration. Â©2006-2016 Asian Research Publishing Network (ARPN).